2018
DOI: 10.1002/lary.27208
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of spontaneous cerebrospinal fistulas and encephaloceles of the temporal bone

Abstract: 4 Laryngoscope, 128:2170-2177, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 35 publications
1
60
0
1
Order By: Relevance
“…Literature has demonstrated that most patients who undergo sCSF‐L repair are obese 1,8,10,13,14,18,19 (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Literature has demonstrated that most patients who undergo sCSF‐L repair are obese 1,8,10,13,14,18,19 (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, there were no infections using bone cement. Prior studies have noted the possibility of infection when using bone cement in the mastoid, although rates of infection were relatively low 14,26,39 . Specifically, Kutz et al utilized bone cement in 82.4% of 55 patients undergoing repair of sCSF‐L 14 ; one patient who underwent transmastoid repair of a posterior fossa defect developed an infection post‐operatively, which resolved after a return to the OR to clear granulation tissue off of the bone cement 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die Pathogenese der beidseitigen Otoliquorrhoe ist in unserem Fall nicht endgültig zu klären, jedoch kann eine tegmentale knöcherne Dehiszenz bereits ab einer Größe von 2 Millimeter als Schwachstelle durch chronische Inflammation im Sinne rezidivierender Mittelohrentzündungen eine mögliche Ursache darstellen. Die Therapie der spontanen Liquorleckage der Laterobasis ist chirurgisch und erfolgt klassischerweise über einen transmastoidalen oder trans-temporalen Zugang [7]. Bei der Liquorleckage der anterioren Schädelbasis stehen dem Chirurgen zusätzlich endonasal-endoskopische Therapieverfahren zur Verfügung [8].…”
Section: Diskussionunclassified